2021
DOI: 10.3991/ijim.v15i18.24539
|View full text |Cite
|
Sign up to set email alerts
|

User Behavioral Intention to Use Online Distance Learning (ODL): The Role of Self-Efficacy and Domain Knowledge

Abstract: <p class="0abstract"><span lang="EN-US">The rise of novel coronavirus 2019 has shifted the roles of education industry. Face-to-face have become a distant memory; students and educators are now heavily relying on the digital communication. Application such as Google Meet, Webex, Webinar, Stream Yard, Zoom, and many more have become the new norm among educators and students. However, the sudden dependency on the digital technologies raises a question on the user intention to use this new digital tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Despite Saudi Arabia, humanity reached its limits in 2020 against natural disasters in the form of the COVID-19 pandemic, where European western countries also tried for e-learning. Among them, Greece was one of the countries that handled this crisis relatively well and was highlighted by the international media [10], whereas Malaysia shifted to an online mode for undergraduates' perception to improve their speaking skills [11]. The user's behavioral intention regarding online distance learning is analyzed in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite Saudi Arabia, humanity reached its limits in 2020 against natural disasters in the form of the COVID-19 pandemic, where European western countries also tried for e-learning. Among them, Greece was one of the countries that handled this crisis relatively well and was highlighted by the international media [10], whereas Malaysia shifted to an online mode for undergraduates' perception to improve their speaking skills [11]. The user's behavioral intention regarding online distance learning is analyzed in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Research that was conducted in [28] found that BYOD had given positive influence on learning and academic achievements of students and BYOD also give impact in stimulating and motivating students that will affect the level of students' performances and creation of independent learning. E-learning users believe that highquality educational services are acceptable, and that a secure atmosphere for these systems might help them feel more useful [29].…”
Section: Byod In Educationmentioning
confidence: 99%
“…Changing organizational and procedural shakeups without proper change management can have long-lasting effects on every organization member. The constant urge to be online and available in all sorts of situations influences both temporary and long-lasting interpersonal and intrapersonal behaviour, as previous research indicates [63], [64]. Furthermore, the adaptation of additional technology, especially smartphone usage can be a detrimental security risk [65]- [67].…”
Section: Practical Implicationsmentioning
confidence: 99%